Two lossy integrator loop based current-mode electronically tunable universal filter employing only grounded capacitors. (January 2017) - Arslanalp, Remzi; Yuce, Erkan; Tola, Abdullah T.
Abstract: In this paper, a novel single-input and multiple-output second-order current-mode universal filter is proposed where lossy integrator blocks, scaling blocks and summing blocks are employed. The proposed filter can simultaneously generate all the five universal filter responses namely; low-pass, high-pass, band-pass, notch and all-pass responses without requiring any critical passive component matching conditions. It uses only two grounded capacitors as passive components and BJTs as active elements; thus, it can be classified as an active-C filter. Both resonance frequency and quality factor of the proposed filter can be tuned electronically. Approximately 1.5 decades adjustable input frequency range for all the universal filter responses and high quality factor for band-pass response are obtained. Obtained PSpice simulation results confirm the theoretical design. Non-ideality and Monte Carlo analyses are also given. A practical realization of the single lossy integrator is accomplished. All the presented results are discussed.